RESEARCH ON THE LAYERING A ALGORITHM FOR REAL-TIME NAVIGATION - Tan, X. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2015)
According to the existing problems in the applications of embedded navigation, this paper designs the hierarchical search A*algorithm, based on the transferring road network, to meet the need of real-time navigation. In the algorithm, a hierarchical search strategy is applied to route programming of large area, yet the duplicate searching A* algorithm, based on the transferring road network, is applied to the path computation, which is able to handle intersection turn restrictions and node weight, with little storage space but fast searching speed. Practically, the algorithm is proved to meet the technological need of real-time navigation both in computing speed and route rationality.